2016
DOI: 10.1002/ijgo.12077
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with maternal mortality among patients meeting criteria of severe maternal morbidity and near miss

Abstract: Among WHO's criteria for severe maternal morbidity and near miss, eclampsia, low oxygen saturation, ICU admission, intubation, mechanical ventilation, and cardiopulmonary resuscitation were most associated with maternal death. Use of magnesium sulfate was a protective factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
2
7
0
7
Order By: Relevance
“…It is important to point out that most studies work with the number of births in the denominator of the maternal morbidity ratio, whereas the WHO recommends using LBs, as we have done in our study. The mortality ratio in the maternal near miss cases was of 18%, which is compatible with what is found in the literature 11,[19][20][21][22] for countries with low and medium socioeconomic levels. It is necessary to develop a public policy to protect maternal and child health throughout all of the care levels to prevent complications or evolution into severe cases.…”
Section: Discussionsupporting
confidence: 90%
“…It is important to point out that most studies work with the number of births in the denominator of the maternal morbidity ratio, whereas the WHO recommends using LBs, as we have done in our study. The mortality ratio in the maternal near miss cases was of 18%, which is compatible with what is found in the literature 11,[19][20][21][22] for countries with low and medium socioeconomic levels. It is necessary to develop a public policy to protect maternal and child health throughout all of the care levels to prevent complications or evolution into severe cases.…”
Section: Discussionsupporting
confidence: 90%
“… * Although the WHO definition for prolonged unconsciousness stipulates any loss of consciousness lasting more than 12 hours, there is evidence that reduced oxygen saturation during loss of consciousness for greater than one hour is associated with maternal death [ 34 ]. …”
Section: Methodsmentioning
confidence: 99%
“…In many developed countries, maternal mortality has declined to single digits, while cases of near misses are more and, therefore, useful for the evaluation of the current system [4][5][6]. 2013 where after social programs it has decreased to 43.3 per 1,000 live births 2; unlike at the international level, it has been observed that MM is overestimated, when evaluating mortality in women of reproductive age.…”
Section: Severe Obstetric Morbidity (Near Miss) Backgroundmentioning
confidence: 99%